Breaking Boundaries: A Review on Rural Women Entrepreneurs Driving Economic Change in India - Dr. Usha N. Patil; Dr. Rajeshkumar U. Sambhe (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Rural women entrepreneurs in India are playing a vital role in driving economic and social change, breaking through traditional barriers to create opportunities for themselves and their communities. This paper explores the landscape of rural women entrepreneurship in India, highlighting the factors that motivate women to start businesses, including economic necessity, government support, and technological advancements. It also examines the significant challenges they face, such as limited access to finance, social and cultural constraints, and inadequate market linkages. Through case studies and success stories, the paper showcases how rural women are not only contributing to household incomes but also fostering community development and shifting gender dynamics. The study concludes with policy recommendations aimed at strengthening support systems, improving access to credit, and enhancing skill development to empower more rural women to become successful entrepreneurs and catalysts for economic growth.